2019
DOI: 10.1177/0269758019872903
|View full text |Cite
|
Sign up to set email alerts
|

‘Some men deeply hate women, and express that hatred freely’: Examining victims’ experiences and perceptions of gendered hate crime

Abstract: Extensive debate about the place of gender within the hate-crime policy domain has been fuelled by national victimisation surveys indicating people’s experiences of ‘gender hate crime’ coupled with Nottinghamshire Police’s decision to begin categorising misogynistic street harassment as a form of hate crime. Drawing on the results of an online survey of 85 respondents, this article explores people’s experiences of gender-related victimisation as ‘hate crimes’. The analysis demonstrates how participants relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…Women with experiences of misogynistic hate crime are, on the other hand, significantly more likely to have been subjected to sexual harassment with a medium effect size. This result is in line with previous research showing that misogynistic crimes often include threats of sexual violence or consist of various forms of sexual harassment (Mason-Bish & Duggan, 2019).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Women with experiences of misogynistic hate crime are, on the other hand, significantly more likely to have been subjected to sexual harassment with a medium effect size. This result is in line with previous research showing that misogynistic crimes often include threats of sexual violence or consist of various forms of sexual harassment (Mason-Bish & Duggan, 2019).…”
Section: Resultssupporting
confidence: 93%
“…Sexual offenses were very common, and the victims often drew the conclusion that the incident was misogynistic since the offenders used derogatory sexual epithets. Like previous studies, Mason-Bish & Duggan (2019) also found an interplay between sexual orientation and gender, as well as a heightened risk for those with transgender or androgynous appearance. The study also indicates that age is a risk factor, as participants described a reduction in victimization frequency as they aged.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations